The Transfer of Japanese-Style Management to American Subsidiaries: Constraints, and Competencies - Beechler, Schon; Yang, John Zhuang (Journal of International Business Studies, 1994)
This paper first reviews the theories of the transfer of Japanese management practices overseas. The paper then outlines a contingency theoretical model that specifies the factors which are hypothesized to impact the transfer of Japanese-style HRM practices to overseas subsidiaries. Qualitative data from a field study of ten Japanese subsidiaries in the U.S., five in the service industry and five in manufacturing, are used to illustrate the concepts presented in the theoretical discussion.